EXTENT OF HETEROSIS OVER ENVIRONMENTS IN RICE HYBRIDS USING CMS SYSTEM - K. PARIMALA; CH. SURENDER RAJU (The Bioscan, 2024)
An experiment was conducted to assess the magnitude of heterosis for grain yield and its attributes by evaluating 60 hybrids at three different locations. The analysis of variance for combining ability over locations revealed presence of significant differences among the locations, genotypes, parents, parents vs. crosses and crosses for all the characters studied. Significant negative standard heterosis was recorded by eleven hybrids over the best check MTU-1010 for days to 50% flowering. The hybrid combinations, IR-58025A x RNR-15038 and IR-58025A x RNR-2781 were found to be most promising for number of productive tillers per plant. As many as 41 crosses showed significant superiority for number of filled grains per panicle and twenty hybrids exhibited positive heterosis for spikelet fertility (%) over the hybrid check KRH-2. The hybrids, IR-58025A x RNR-15038, IR 79156A x NWGR-3132, IR-58025A x RNR-2781 and IR-79156A x RNR-2781 expressed highly significant positive heterosis for grain yield per plant over standard checks and these hybrids also proved its performance in productive tillers per plant, panicle length and number of filled grains per panicle. The potentiality of those hybrids could be further evaluated in multi-locational trials for commercial cultivation.